Investigating Water Balance Configuration in the Urban Areas of Mthatha, South Africa - Phelokazi S.; Amoo O.T.; Ikudayisi A.; Nakin MDV. (Selected Scientific Papers: Journal of Civil Engineering)
Considering urbanization’s effects, quantifying individual components of the hydrological cycle, especially at the catchment scale, has been challenging due to the influence of climate change and human activities. Accordingly, the study assesses the impacts of Land Use and Land Cover Changes (LULCC) on the water quantity degradation. It evaluates the effect of urbanization on water balance configuration between the period 2000-2020. The resultant result of LULC reflected a long-term increase in bare land by 11.72% and a marginal increase in built-up areas (0.52%). In contrast, the annual water balance results show an annual negative water deficit ranging from −19.40 mm to −624.955 mm. The result has demonstrated the use of QSWAT and SWMM in a Quick geographic information systems (QGIS) environment to drive the socio-hydrological framework to model spatially distributed and time-varying hydrologic and meteorologic datasets as an effective scientific visualization technique in water balance evaluation.